God's Punishment for Those Who Leave Prayer (Content Analysis of Nazam Tarikus-Salat in the Book of Aqaid Iman) - Riri Safitri (Journal of Islamic History and Manuscript)
Nazam Tarikus-Salat (NTS) is a Sundanese Pegon script that belongs to a nadoman or praise poem. NTS is one of the chapters in the text of Aqaid Iman. The research of NTS has two main aims: 1) Producing the clean text edits from reliable copying and writing errors. Moreover, it can be used as a source of research in other fields of science with using manuscripts as the source of information. 2) Describing the religious values ​​contained in NTS in order to give the benefit to the society. To achieve the above aims, it has been applied several theories namely the philology theory and the Quranic intertextuality. The philology theory relates with the text edits. The text editing method used is the standard method, which is to publish the manuscript by correcting small errors. The method used in the research is the method of textual research and the text editing method. The method of the study of the manuscript includes the determination of a single manuscript and a manuscript description. The text editing method in the form of presenting text edits with the critical apparatus without changing its authenticity. The intertextuality used in NTS is more emphasized on the religious values ​​contained in the text. NTS gives an explanation of the God’s punishment for the person who left the salat. By the NTS text, people understand more about the importance of salat because the punishment that will befall people who do not salat is really heavy. In the NTS text, it was described there are fifteen punishments that will be obtained by humans. The punishments are six in the world, three at dead, three in the grave, and three in the Judgment Day.